PENERAPAN BYL’s GAME DEVELOPMENT LIFE CYCLE DALAM PERANCANGAN VIDEO GAME ORACLE FOR ANGEL - Mustofa Mustofa; Vadlya Ma’arif; Ragil Wijianto; Frengki Pernando (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
The dynamic world development has accelerated the development of technology and information. Computers that were once made only to help humans, but now developed into a means of entertainment, games, communication, etc. In the entertainment sector, Industries’s attention is centered on the video game industry. However, knowledge about making video games is not popular in Indonesia. Based on knowledge about the life cycle in designing video games. Therefore this research tries to apply the Cycle Life Development Game compiled by Penny de Byl in designing RPG video games (Role Playing Game). The design of this video game uses the application of 3 dimensional Blender Game Engine. By using the Game Development Life Cycle provided by Byl this video game can be finished well